Incorporating Nutrition Counseling into Lifestyle Medicine. Issue 3 (May 2022) - Cepni, Aliye B.; Crumbley, Christine; Nadeem, Saad; Ledoux, Tracey A.; Johnston, Craig A.
Despite considerable evidence that plant-based diets can significantly improve health, medical professionals seldom discuss this with their patients. This issue might occur due to minimal training received in medical education, lack of time, and low self-efficacy for counseling patients about diet. Nutrition and lifestyle change should be considered a core competency for all physicians and health professionals looking for cost-effective ways to improve patient health outcomes and reduce nutrition-related chronic diseases. Strategies for health professionals to acquire nutrition counseling skills in medical training and clinical practices are discussed.